Bookstore cat - Wheeler, Cindy (New York : Random House, 1994)
Mulligan, the bookstore cat, has an exciting day when a pigeon wanders into the store.
"Preschool-grade 1"--Cover.
1.8
K-3
K-3
Elem. School Library Collection
School Library Journal
Keywords: Cats -- Fiction; Bookstores -- Fiction; Cats -- Fiction; Bookstores -- Fiction